2(2x+2)-5x=5-6(x-4)

Simple and best practice solution for 2(2x+2)-5x=5-6(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x+2)-5x=5-6(x-4) equation:



2(2x+2)-5x=5-6(x-4)
We move all terms to the left:
2(2x+2)-5x-(5-6(x-4))=0
We add all the numbers together, and all the variables
-5x+2(2x+2)-(5-6(x-4))=0
We multiply parentheses
-5x+4x-(5-6(x-4))+4=0
We calculate terms in parentheses: -(5-6(x-4)), so:
5-6(x-4)
determiningTheFunctionDomain -6(x-4)+5
We multiply parentheses
-6x+24+5
We add all the numbers together, and all the variables
-6x+29
Back to the equation:
-(-6x+29)
We add all the numbers together, and all the variables
-1x-(-6x+29)+4=0
We get rid of parentheses
-1x+6x-29+4=0
We add all the numbers together, and all the variables
5x-25=0
We move all terms containing x to the left, all other terms to the right
5x=25
x=25/5
x=5

See similar equations:

| 1/3-2/3m=2/3m+2/3 | | 24y4=4y2 | | 3–-4v=11 | | 6x+12=9x+15 | | 2(5c+2)-2c=3(2c+3+7 | | 17=-5w+2(w+5) | | 5x+5=3(5x-4)-10x* | | −7x=21 | | 8x100=8x100= | | k/9-23=-4 | | r/4-3=13 | | x=154= | | 2(x+1)=14x-6 | | X+a(-7)=23 | | 120x-1000+33x=64 | | -a+8=-1 | | 9v+2=65 | | 4=-10+w/2 | | 2h−8=h+17 | | −15+7.5(2d−1)=7.5​ | | (-3x)6=12 | | 70+3x+2=9x+6 | | 3x–75x=–3 | | A-92=105a= | | 9-4j=9+3j | | x=154 | | x/3=46= | | (5=7s-9 | | 0=0.4n^2+0.6n-378 | | 2=y/7-1 | | x=-1+1/15 | | 48=18-4+8w |

Equations solver categories